«Denikin’s» Church Council in works on latest Russian archeography - V. V. Kalinovsky; I. V. Petrov; A. S. Puchenkov (Омский научный вестник: Серия "Общество. История. Современность")
The authors performed the detailed analysis of collection of documents covering the work of the Southeast Cathedral in 1919 compiled by a specialist in the history of the Russian Orthodox Church in the 1920s and 1930s. Yu. A. Biryukova. A special place in the article is given to the sources and historiography of the problem, as well as to the advantages and disadvantages that the publication contains (primarily in the context of the author’s substantial limitation of his own conclusions and the lack of a concept for the history of the development of Russian parish life during the Civil War)